2017
DOI: 10.3390/ijerph14101129
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Titanium and Zirconium Ions in Water by MPT-LTQ Mass Spectrometry in Negative Mode

Abstract: Microwave plasma torches (MPTs) can be used as simple and low power-consumption ambient ion sources. When MPT-mass spectrometry (MPT-MS) is applied in the detection of some metal elements, the metallic ions exhibit some novel features which are significantly different with those obtained by the traditional inductively coupled plasma (ICP)-mass spectrometry (ICP-MS) and may be helpful for metal element analysis. As the representative elements of group IVA, titanium and zirconium are both of importance and value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…MPTs can be used as simple and low-power-consumption ambient ion sources. In the work of Yang et al (2017), MPT was used in combination with a linear ion trap MS. Under the optimized conditions, the LOD was estimated to be at the level 20 μg/l for zirconium, with linear dynamics range 20-200 μg/l.…”
Section: Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%
“…MPTs can be used as simple and low-power-consumption ambient ion sources. In the work of Yang et al (2017), MPT was used in combination with a linear ion trap MS. Under the optimized conditions, the LOD was estimated to be at the level 20 μg/l for zirconium, with linear dynamics range 20-200 μg/l.…”
Section: Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%
“…1f) is consistent with the reported test results. 28 The strong band located near 1009.9 cm −1 originates from the asymmetrical (P–O) stretching and the covalence of the Ti–O interaction is supported by the clear appearance of the totally symmetric stretching near 326.1 cm −1 .…”
Section: Resultsmentioning
confidence: 93%
“…After a long time, Ti-Qiang Zhang as well as Zhi-Qiang Zhu [ 22 , 23 , 132 ] studied the direct desorption/ionization approach of MPT on a linear ion trap (LTQ) mass spectrometer to analyze a series of small organic molecules, and they showed that MPT is a useful alternative ambient ion source. Zhi-Qiang Zhu’s group [ 24 , 25 , 26 , 133 , 134 , 135 , 136 ] has also completed a lot of work on the detection of trace metal in aqueous solutions by MPT source, coupled with a mass spectrometer (MPT-MS), reaching an in-depth understanding of the characteristics of MPT.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…After starting with a brief review on the hazards, migration, distribution and traditional analysis methods of PAHs which are widely used in recent years, including liquid chromatography, gas chromatography and surface enhanced Raman spectroscopy and so on, we mainly want to present the applications of the modern ambient mass spectrometry in the detection of PAHs; in addition, we present the far out novel results in our lab by using microwave plasma torch (MPT) mass spectrometry, which exhibited the versatility of MPT MS as a platform in the research of PAHs. MPT ion source is a novel ambient ion generator and has multiple advantages, for example, simple construction of the device and easy operation, low power dissipation, relative high sensitivity, and suitable for many types of samples including metal elements and organic samples [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%